Preparation process of thick film circuit board based on thick film copper metal ceramic
Through the multi-stage copper particles arrangement and specific process processing, a thick-film copper cermet-based thick-film circuit board with excellent adhesion and conductivity was prepared, which solved the problems of high resistance and poor adhesion of the thick-film copper layer in the prior art.
Patent Information
- Application Number
- CN202411949254.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing thick film copper circuit boards have problems with high porosity, poor uniformity and density after sintering, resulting in high resistance and poor adhesion.
By setting up multi-stage copper particles, binders for specific segments are prepared and adaptive solvents are prepared to form thick-film copper slurry. The sintering process is optimized by using calcination treatment with specific heating rates and multi-stage temperatures, in conjunction with the use of copper-based graphene and glass powder.
It effectively improves the adhesion and conductivity of thick-film copper cermet-based thick-film circuit board, and improves its quality and application.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of circuit boards, in particular to a preparation process of a thick film copper metal ceramic-based thick film circuit board. Background Art
[0002] Thick film circuit boards are widely used in the electronics industry due to their excellent electrical properties, high reliability, high thermal conductivity, etc. Among them, thick film copper metal ceramic-based circuit boards are a special type of thick film circuit boards; they combine the excellent conductivity of copper metal and the high heat resistance of ceramic substrates to meet the needs of high-performance electronic products.
[0003] Thick film circuit boards are generally made by coating a conductive paste on a ceramic substrate through a printing process and sintering it. In copper-based thick film circuit boards, the preparation and sintering process of thick film copper paste are key technologies that affect the conductivity, adhesion and other properties of thick film circuit boards. In the prior art, thick film copper paste is prepared from copper particles, organic carriers, and glass powder; common copper particles are generally copper powders of about 5μm, but a single, larger copper powder paste has the disadvantages of high porosity, poor uniformity and density after sintering, resulting in high resistance and poor adhesion of the thick film copper layer. On the other hand, organic carriers generally include solvents and binders. Common binders have a high residual carbon rate after sintering, which affects the conductivity of the thick film copper layer; binders generally do not promote the dispersion of inorganic matter, resulting in unevenness, which affects the quality of the thick film copper layer.
[0004] In summary, it is of great significance to solve the above problems and prepare a thick film circuit board based on thick film copper metal ceramic. Summary of the invention
[0005] The object of the present invention is to provide a preparation process of a thick film circuit board based on a thick film copper metal ceramic substrate to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A preparation process of a thick film copper metal ceramic-based thick film circuit board comprises the following steps:
[0008] Step 1: (1) washing copper particles in dilute hydrochloric acid, deionized water, and ethanol in turn; obtaining pretreated copper particles; (2) adding a binder to a solvent and stirring evenly under a nitrogen atmosphere to obtain an organic carrier; adding the pretreated copper particles, stirring at a temperature of 40 to 50° C. for 20 to 30 minutes; adding glass powder and grinding and mixing; obtaining a thick film copper slurry;
[0009] Step 2: Print the copper paste evenly on the ceramic substrate; place it in a sintering furnace, in a nitrogen atmosphere, and pre-bake at 150-160°C for 10-30 minutes; heat it to 220-230°C and bake it for 10-30 minutes; heat it to 450-550°C and calcine it for 30-40 minutes; heat it to 800-900°C and calcine it for 20-30 minutes; cool it and place it at room temperature for 1-2 hours to form a thick film copper layer; and obtain a thick film circuit board.
[0010] More optimally, the raw materials of the thick film copper paste include the following substances: by weight, 74 to 76 parts of copper particles, 4 to 6 parts of glass powder, 3 to 6 parts of binder, and 14 to 17 parts of solvent.
[0011] More optimally, the copper particles include 1±0.5 μm copper powder, 50±20 nm copper powder, and copper-based graphene in a mass ratio of (2.8-2.9):1:(0.1-0.2).
[0012] More optimally, the preparation method of the copper-based graphene is: urea and graphene oxide are added to deionized water in sequence, dispersed evenly, and hydrothermally reacted at 120-150° C. for 6-12 hours; washed, dried, and ground to obtain nitrogen-doped graphene; ultrasonically dispersed in dimethylformamide, copper nitrate, titanium tetrachloride, and boric acid are added and stirred evenly; placed in a microwave reactor, under a nitrogen atmosphere, set the power to 800-1000 W, and heated for 1-3 minutes; filtered, washed, and dried to obtain copper-based graphene.
[0013] More optimally, in the raw material of the nitrogen-doped graphene, the mass ratio of urea to graphene oxide is 2-3:1; in the raw material of the copper-based graphene, the ratio of nitrogen-doped graphene, copper nitrate, titanium tetrachloride, and boric acid is 1:(1.5-1.8):(0.1-0.2):(0.3-0.5).
[0014] More optimally, the preparation method of the adhesive is as follows: (1) under a nitrogen atmosphere, methyl methacrylate, acrylamide, 2-butyl methacrylic acid, and azobisisobutyronitrile are added to toluene in sequence, the temperature is set to 60-80°C, and the reaction is stirred for 2-4 hours; cysteine is added dropwise, and the reaction is continued for 1-2 hours; the product is washed with n-hexane and dried to obtain an acrylic copolymer; (2) the acrylic copolymer is added to dimethylformamide, an epoxy silane coupling agent is added, the reaction is stirred at 80-85°C for 1-2 hours, and the reaction is washed and dried to obtain an adhesive.
[0015] More optimally, in the raw materials of the acrylic copolymer, the molar ratio of methyl methacrylate, acrylamide, 2-butyl methacrylic acid and cysteine is (35-38):(4-7):58:3; in the raw materials of the adhesive, the mass ratio of the acrylic copolymer to the epoxy silane coupling agent is 1:0.1-0.2.
[0016] More optimally, the solvent comprises dimethylformamide, pinene alcohol, diethylene glycol butyl ether and deionized water in a mass ratio of 50:(40-43):(5-8):2.
[0017] More optimally, the heating rate of the pre-baking is 5-6°C / min; the heating rate of the intermediate baking is 10-15°C / min; the heating rate of the primary calcination is 65-75°C / min; and the heating rate of the secondary calcination is 50-60°C / min.
[0018] Preferably, the thickness of the thick copper layer is 30-80 μm.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are: through the multi-level copper particle setting, a binder of a specific chain segment is prepared, and an adaptive solvent is formulated to form a thick film copper slurry; and a specific heating rate and multi-level temperature calcination treatment are coordinated to effectively maximize the adhesion and conductivity of the thick film copper metal ceramic-based thick film circuit board, thereby improving its quality and applicability.
[0020] In the scheme, the copper particles include micron-sized copper powder, nano-sized copper powder and copper-based graphene. The multi-stage preparation effectively improves the uniformity of the slurry and the printing performance, thereby forming a smooth coating; the nano-sized copper powder is effectively filled in the gaps of the micron-sized copper powder, effectively improving the compactness after sintering and inhibiting the crack tendency, thereby improving the manufacturing efficiency and the stability of the thick copper layer. On the other hand, the scheme introduces copper-based graphene as a conductive enhancement phase to effectively reduce resistance and improve conductivity. In the scheme, in order to improve the dispersibility of graphene in copper powder, improve its interface with copper powder, and maximize the enhanced performance. By nitrogen doping graphene oxide, and then pre-negative copper ions and titanium ions on its surface; by microwave doping, reduced metal-doped graphene is obtained. Among them, the pre-doping of copper can improve the fluidity of graphene during the sintering process of copper powder, and increase its uniform dispersion and interface in the thick copper layer. On the other hand, the introduction of boric acid can promote the loading of copper and titanium, and the boron content can improve the oxidation resistance during the sintering process and enhance the mechanical properties of the thick copper layer. The introduction of low-content titanium can improve the dimensional stability of copper grains during sintering, thereby ensuring high conductivity.
[0021] In the scheme, a binder with a specific chain segment is prepared, which is first obtained by copolymerizing methyl methacrylate, acrylamide, and 2-butyl-methacrylic acid in a specific ratio to obtain an acrylic copolymer; and then prepared by using an amino-grafted epoxy silane coupling agent. Among them, by limiting the molar amounts of methyl methacrylate, acrylamide, and 2-butyl-methacrylic acid, the sintering property is maximized and the residual carbon rate is reduced on the basis of ensuring their wettability to copper particles. Among them, methyl methacrylate should not be too much, as too much will increase the residual carbon rate and increase resistance. 2-Butyl-methacrylic acid is more likely to produce rapid pyrolysis due to the butyl group; at the same time, the carboxyl group it contains can form a complex with metal ions; and the grafted cysteine and the subsequent grafted silane coupling agent can effectively disperse the nanoparticles, inhibit aggregation, and evenly disperse the copper particles. Improve the film-forming property of the thick film copper paste, increase the flatness; and the adhesion of the thick film copper layer.
[0022] In the scheme, the solvent is optimized based on the binder, copper particles, and glass powder. The solvent has high wettability for copper particles and glass powder, which is beneficial to dispersibility and sintering uniformity. In addition, the modified solvent can dissolve the binder well, thereby improving the film quality, and because of its good solubility, it can effectively reduce thermal degradation residues. Among them, the solvents include dimethylformamide, pineneol, diethylene glycol butyl ether, and deionized water; deionized water and dimethylformamide are low-boiling point solvents, so the previous pre-baking can be effectively volatilized, and the heating rate in the process should not be too high. Too high will lead to a faster volatilization rate, resulting in a large amount of exhaust and increased porosity. Then increase the temperature to the medium baking temperature to volatilize the higher boiling point pineneol and diethylene glycol butyl ether; volatilize in layers in turn, so that on the basis of effectively ensuring wettability, combined with subsequent multi-step sintering to reduce the residual carbon rate of the binder, and ensure the quality of the thick film copper layer.
[0023] In the scheme, the pyrolysis of the coagulant starts at about 160°C, and the pyrolysis platform is around 270°C and 350°C. After the intermediate baking, a faster heating rate is used to decompose the binder to improve the fluidity of the glass powder and increase the wettability of the subsequent glass powder to the copper particles; at the same time, a faster temperature rise sintering can reduce the residual amount of the binder; thereby improving the adhesion and density of the copper layer and the conductivity of the thick film circuit board. After the first calcination, the organic carrier is basically completely pyrolyzed, and there is less residue. Continue to heat up to the secondary calcination temperature. The temperature should be slightly lowered during this stage of heating, so as to reduce the pores, increase the wetting of the glass powder to the copper particles, and improve the adhesion and density. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] It should be noted that the following parts are calculated by weight, and the purchase manufacturers of all raw materials involved in the present invention are exemplary included without any special restrictions: in the following embodiments, the initial melting temperature of the glass powder is 430°C, the model is FR01, and the mesh size is 2000 mesh; the model of the 1μm copper powder is XH-Cu-001, and the brand is Xiaohuang Nano; the brand of the 50nm copper powder is YB-1, and the brand is Yinbai; the average thickness of the graphene oxide is 1.5nm, and the brand is Zhitai; the copper nitrate is copper nitrate trihydrate, the CAS number of methyl methacrylate is 80-62-6, the CAS number of acrylamide is 79-06-1, the CAS number of 2-butyl-methacrylic acid is 97-86-9, the CAS number of cysteine is 52-90-4, and other raw materials are commercially purchased; in the following embodiments, the thickness of the thick film copper layer is 50μm;
[0026] Embodiment 1: A process for preparing a thick film circuit board based on a thick film copper metal ceramic substrate, comprising the following steps:
[0027] Pre-preparation: urea and graphene oxide in a mass ratio of 3:1 are added to deionized water in sequence and dispersed evenly, and hydrothermally reacted at 150°C for 8 hours; washed, dried and ground to obtain nitrogen-doped graphene; 10 parts of nitrogen-doped graphene are ultrasonically dispersed in 100 parts of dimethylformamide, and 16 parts of copper nitrate, 1.5 parts of titanium tetrachloride and 4 parts of boric acid are added and stirred evenly; placed in a microwave reactor, under a nitrogen atmosphere, set the power to 1000W, and heated for 3 minutes; filtered, washed and dried to obtain copper-based graphene;
[0028] Under nitrogen atmosphere, methyl methacrylate, acrylamide and 2-butyl methacrylic acid in a molar ratio of 36:6:58 are added to toluene in sequence, and azobisisobutyronitrile (the amount added is 2wt% of the mixed monomers) is added; the temperature is set to 75°C and stirred for reaction for 3 hours; cysteine (the molar ratio of 2-butyl methacrylic acid to cysteine is 58:3) is added dropwise, and the reaction is continued for 1 hour; the product is washed with n-hexane and dried to obtain an acrylic copolymer; (2) 10 parts of the acrylic copolymer are added to dimethylformamide, 1.5 parts of epoxy silane coupling agent KH560 are added, the reaction is stirred at 80°C for 2 hours, washed and dried to obtain a binder;
[0029] Step 1: 75 parts of copper particles (1 μm copper powder, 50 nm copper powder, copper-based graphene in a ratio of 2.84:1:0.16) were placed in a 5 wt % dilute hydrochloric acid aqueous solution and ultrasonicated for 10 minutes, and then rinsed with deionized water and ethanol in turn to obtain pretreated copper particles;
[0030] Under a nitrogen atmosphere, 4 parts of a binder were added to 16 parts of a solvent (50:42:6:2 of dimethylformamide, pinene alcohol, diethylene glycol butyl ether, and deionized water) and stirred evenly to obtain an organic vehicle; pretreated copper particles were added and stirred at 45°C for 30 minutes; 5 parts of glass powder were added and ground and mixed to obtain a thick film copper slurry;
[0031] Step 2: Print the copper slurry evenly on the ceramic substrate; place it in a sintering furnace, under a nitrogen atmosphere, set the heating rate to 5℃ / min at room temperature, heat it to 160℃ for pre-baking for 20 minutes; set the heating rate to 15℃ / min, heat it to 225℃ and bake it for 20 minutes; set the heating rate to 70℃ / min, heat it to 520℃ and calcine it for 30 minutes; set the heating rate to 55℃ / min, heat it to 880℃ and calcine it for 30 minutes; cool it, and place it at room temperature for 2 hours to form a thick film copper layer; and obtain a thick film circuit board.
[0032] Embodiment 2: A process for preparing a thick film circuit board based on a thick film copper metal ceramic substrate, comprising the following steps:
[0033] Pre-preparation: urea and graphene oxide in a mass ratio of 3:1 are added to deionized water in sequence and dispersed evenly, and hydrothermally reacted at 150°C for 8 hours; washed, dried and ground to obtain nitrogen-doped graphene; 10 parts of nitrogen-doped graphene are ultrasonically dispersed in 100 parts of dimethylformamide, and 16 parts of copper nitrate, 1.5 parts of titanium tetrachloride and 4 parts of boric acid are added and stirred evenly; placed in a microwave reactor, under a nitrogen atmosphere, set the power to 1000W, and heated for 3 minutes; filtered, washed and dried to obtain copper-based graphene;
[0034] Under nitrogen atmosphere, methyl methacrylate, acrylamide and 2-butyl methacrylic acid in a molar ratio of 36:6:58 are added to toluene in sequence, and azobisisobutyronitrile (the amount added is 2wt% of the mixed monomers) is added; the temperature is set to 75°C and stirred for reaction for 3 hours; cysteine (the molar ratio of 2-butyl methacrylic acid to cysteine is 58:3) is added dropwise, and the reaction is continued for 1 hour; the product is washed with n-hexane and dried to obtain an acrylic copolymer; (2) 10 parts of the acrylic copolymer are added to dimethylformamide, 1.5 parts of epoxy silane coupling agent KH560 are added, the reaction is stirred at 80°C for 2 hours, washed and dried to obtain a binder;
[0035] Step 1: 74 parts of copper particles (1 μm copper powder, 50 nm copper powder, copper-based graphene in a ratio of 2.9:1:0.1) were placed in a 5 wt % dilute hydrochloric acid aqueous solution and ultrasonicated for 10 minutes, and then rinsed with deionized water and ethanol in turn to obtain pretreated copper particles;
[0036] Under a nitrogen atmosphere, 3 parts of a binder were added to 14 parts of a solvent (50:40:8:2 of dimethylformamide, pinene alcohol, diethylene glycol butyl ether, and deionized water) and stirred evenly to obtain an organic carrier; pretreated copper particles were added and stirred at 45°C for 30 minutes; 4 parts of glass powder were added and ground and mixed to obtain a thick film copper slurry;
[0037] Step 2: Print the copper slurry evenly on the ceramic substrate; place it in a sintering furnace, under a nitrogen atmosphere, set the heating rate to 5℃ / min at room temperature, heat it to 160℃ for pre-bake for 20 minutes; set the heating rate to 15℃ / min, heat it to 225℃ and bake it for 20 minutes; set the heating rate to 70℃ / min, heat it to 450℃ and calcine it for 30 minutes; set the heating rate to 55℃ / min, heat it to 900℃ and calcine it for 30 minutes; cool it, and place it at room temperature for 2 hours to form a thick film copper layer; obtain a thick film circuit board.
[0038] Embodiment 3: A process for preparing a thick film circuit board based on a thick film copper metal ceramic substrate, comprising the following steps:
[0039] Pre-preparation: urea and graphene oxide in a mass ratio of 3:1 are added to deionized water in sequence and dispersed evenly, and hydrothermally reacted at 150°C for 8 hours; washed, dried and ground to obtain nitrogen-doped graphene; 10 parts of nitrogen-doped graphene are ultrasonically dispersed in 100 parts of dimethylformamide, and 16 parts of copper nitrate, 1.5 parts of titanium tetrachloride and 4 parts of boric acid are added and stirred evenly; placed in a microwave reactor, under a nitrogen atmosphere, set the power to 1000W, and heated for 3 minutes; filtered, washed and dried to obtain copper-based graphene;
[0040] Under nitrogen atmosphere, methyl methacrylate, acrylamide and 2-butyl methacrylic acid in a molar ratio of 36:6:58 are added to toluene in sequence, and azobisisobutyronitrile (the amount added is 2wt% of the mixed monomers) is added; the temperature is set to 75°C and stirred for reaction for 3 hours; cysteine (the molar ratio of 2-butyl methacrylic acid to cysteine is 58:3) is added dropwise, and the reaction is continued for 1 hour; the product is washed with n-hexane and dried to obtain an acrylic copolymer; (2) 10 parts of the acrylic copolymer are added to dimethylformamide, 1.5 parts of epoxy silane coupling agent KH560 are added, the reaction is stirred at 80°C for 2 hours, washed and dried to obtain a binder;
[0041] Step 1: 76 parts of copper particles (1 μm copper powder, 50 nm copper powder, copper-based graphene in a ratio of 2.8:1:0.2) were placed in a 5 wt % dilute hydrochloric acid aqueous solution and ultrasonicated for 10 minutes, and then rinsed with deionized water and ethanol in turn to obtain pretreated copper particles;
[0042] Under a nitrogen atmosphere, 6 parts of a binder were added to 17 parts of a solvent (50:43:5:2 of dimethylformamide, pinene alcohol, diethylene glycol butyl ether, and deionized water) and stirred evenly to obtain an organic carrier; pretreated copper particles were added and stirred at 45°C for 30 minutes; 6 parts of glass powder were added and ground and mixed to obtain a thick film copper slurry;
[0043] Step 2: Print the copper slurry evenly on the ceramic substrate; place it in a sintering furnace, under a nitrogen atmosphere, set the heating rate to 5℃ / min at room temperature, heat it to 160℃ for pre-bake for 20 minutes; set the heating rate to 15℃ / min, heat it to 225℃ and bake it for 20 minutes; set the heating rate to 70℃ / min, heat it to 550℃ and calcine it for 30 minutes; set the heating rate to 55℃ / min, heat it to 900℃ and calcine it for 30 minutes; cool it, and place it at room temperature for 2 hours to form a thick film copper layer; obtain a thick film circuit board.
[0044] Comparative Example 1: Based on Example 1, the microwave reaction method in the preparation of copper-based graphene is replaced by a calcination method; the rest is the same as Example 1; the specific differences are as follows:
[0045] Urea and graphene oxide in a mass ratio of 3:1 are sequentially added to deionized water and dispersed evenly, and hydrothermally reacted at 150°C for 8 hours; washed, dried and ground to obtain nitrogen-doped graphene; 10 parts of nitrogen-doped graphene are ultrasonically dispersed in 100 parts of dimethylformamide, 16 parts of copper nitrate, 1.5 parts of titanium tetrachloride and 4 parts of boric acid are added and stirred for 3 to 6 hours; after drying, it is placed in a nitrogen atmosphere, calcined at 200°C for 2 hours, and cooled to obtain copper-based graphene.
[0046] Comparative Example 2: Based on Example 1, the amount of copper-based graphene introduced is increased; the rest is the same as Example 1; the specific differences are as follows:
[0047] Step 1: 75 parts of copper particles (1 μm copper powder, 50 nm copper powder, copper-based graphene in a ratio of 2.7:1:0.3) were placed in a 5 wt % dilute hydrochloric acid aqueous solution and ultrasonicated for 10 minutes, and then rinsed with deionized water and ethanol in turn to obtain pretreated copper particles;
[0048] Under a nitrogen atmosphere, 4 parts of a binder were added to 16 parts of a solvent (50:42:6:2 of dimethylformamide, pineneol, diethylene glycol butyl ether, and deionized water) and stirred evenly to obtain an organic carrier; pretreated copper particles were added and stirred at 45°C for 30 minutes; 5 parts of glass powder were added and ground and mixed; a thick film copper slurry was obtained.
[0049] Comparative Example 3: Based on Example 1, in the preparation of the binder, the molar amounts of methyl methacrylate and 2-butyl-methacrylic acid were exchanged; the rest was the same as Example 1; the specific differences are as follows:
[0050] Under nitrogen atmosphere, methyl methacrylate, acrylamide and 2-butyl methacrylic acid in a molar ratio of 58:6:36 are added to toluene in sequence, and azobisisobutyronitrile (the amount added is 2wt% of the mixed monomer) is added; the temperature is set to 75°C and stirred for reaction for 3 hours; cysteine (the molar ratio of 2-butyl methacrylic acid to cysteine is 58:3) is added dropwise, and the reaction is continued for 1 hour; the product is washed with n-hexane and dried to obtain an acrylic copolymer; (2) 10 parts of the acrylic copolymer are added to dimethylformamide, 1.5 parts of epoxy silane coupling agent KH560 are added, the reaction is stirred at 80°C for 2 hours, washed and dried to obtain a binder.
[0051] Comparative Example 4: Based on Example 1, the solvent was adjusted, dimethylformamide was not introduced, and pre-baking was not performed. The specific differences are as follows:
[0052] Step 1: 75 parts of copper particles (1 μm copper powder, 50 nm copper powder, copper-based graphene in a ratio of 2.84:1:0.16) were placed in a 5 wt % dilute hydrochloric acid aqueous solution and ultrasonicated for 10 minutes, and then rinsed with deionized water and ethanol in turn to obtain pretreated copper particles;
[0053] Under nitrogen atmosphere, 4 parts of binder were added to 16 parts of solvent (93:5:2 of pinene alcohol, diethylene glycol butyl ether, deionized water) and stirred evenly to obtain an organic vehicle; pretreated copper particles were added and stirred at 45°C for 30 minutes; 5 parts of glass powder were added and ground and mixed to obtain a thick film copper slurry;
[0054] Step 2: Print the copper slurry evenly on the ceramic substrate; place it in a sintering furnace, under a nitrogen atmosphere, set the heating rate to 15℃ / min at room temperature, heat it to 225℃ and bake it for 20 minutes; set the heating rate to 70℃ / min, heat it to 520℃ and calcine it for 30 minutes; set the heating rate to 55℃ / min, heat it to 880℃ and calcine it for 30 minutes; cool it, and place it at room temperature for 2 hours to form a thick film copper layer; obtain a thick film circuit board.
[0055] Performance Test 1: The thick film circuit boards prepared in the examples and comparative examples were subjected to relevant performance tests; based on the standard method of GB / T17473.3: (1) using a digital ohmmeter to test the square resistance of the thick film copper layer; (2) using a spiral puller and soldering a lead wire section on its surface (2×2 mm 2 ), and use a tensile machine to test its adhesion; the obtained data are shown in the following table:
[0056] sample Square resistance (mΩ / □) <![CDATA[Adhesion force (N / cm 2 )]]> Example 1 2.38 24.7 Example 2 2.43 24.2 Example 3 2.46 24.0 Comparative Example 1 2.56 23.3 Comparative Example 2 2.60 22.5 Comparative Example 3 2.91 22.1 Comparative Example 4 2.87 23.2
[0057] Conclusion: From the data in the above table, it can be seen that: the present application obtains a thick-film copper metal ceramic-based thick-film circuit board with conductivity and adhesion by optimizing copper particles, binders and corresponding solvents. From the data of comparative example 1, it can be seen that: compared with the roasting process, the microwave reaction method can obtain better dispersed copper-based graphene with low surface defects, so that the thick-film circuit board has better conductivity and adhesion; in comparative example 2, due to the high content of copper-based graphene, the uniform dispersion is reduced, resulting in a decrease in performance; in comparative example 3, due to the exchange of the molar amounts of methyl methacrylate and 2-butyl-methacrylate in the binder, the residual carbon content is increased, resulting in an increase in square resistance; in comparative example 4, due to the adjustment of the solvent and pre-baking steps, the surface pore distribution is deteriorated, resulting in a decrease in the quality of the thick-film copper layer, a decrease in adhesion, and an increase in square resistance.
[0058] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing a thick film circuit board based on a thick film copper metal ceramic substrate, characterized in that: The following steps are involved: Step 1: (1) washing the copper particles in dilute hydrochloric acid, deionized water, and ethanol in sequence; obtaining pretreated copper particles; (2) Under a nitrogen atmosphere, a binder is added to a solvent and stirred evenly to obtain an organic carrier; pretreated copper particles are added, and the temperature is set to 40 to 50° C. and stirred for 20 to 30 minutes; glass powder is added and ground and mixed to obtain a thick film copper slurry; Step 2: Print the copper paste evenly on the ceramic substrate; place it in a sintering furnace, in a nitrogen atmosphere, and pre-bake at 150-160°C for 10-30 minutes; heat it to 220-230°C and bake it for 10-30 minutes; heat it to 450-550°C and calcine it for 30-40 minutes; heat it to 800-900°C and calcine it for 20-30 minutes; cool it and place it at room temperature for 1-2 hours to form a thick film copper layer; and obtain a thick film circuit board.
2. A process for preparing a thick film circuit board based on thick film copper metal ceramic according to claim 1, characterized in that: The raw materials of the thick film copper paste include the following substances: by weight, 74 to 76 parts of copper particles, 4 to 6 parts of glass powder, 3 to 6 parts of binder, and 14 to 17 parts of solvent.
3. The process for preparing a thick film circuit board based on thick film copper metal ceramic according to claim 1, characterized in that: The copper particles include 1±0.5 μm copper powder, 50±20 nm copper powder and copper-based graphene in a mass ratio of (2.8-2.9):1:(0.1-0.2).
4. The process for preparing a thick film circuit board based on thick film copper metal ceramic according to claim 3, characterized in that: The preparation method of the copper-based graphene is as follows: urea and graphene oxide are added to deionized water in sequence, dispersed evenly, and hydrothermally reacted at 120-150° C. for 6-12 hours; washed, dried, and ground to obtain nitrogen-doped graphene; ultrasonically dispersed in dimethylformamide, and copper nitrate, titanium tetrachloride, and boric acid are added and stirred evenly; placed in a microwave reactor, under a nitrogen atmosphere, the power is set to 800-1000 W, and heated for 1-3 minutes; filtered, washed, and dried to obtain the copper-based graphene.
5. The process for preparing a thick film circuit board based on thick film copper metal ceramic according to claim 4, characterized in that: In the raw material of the nitrogen-doped graphene, the mass ratio of urea to graphene oxide is 2-3:1; in the raw material of the copper-based graphene, the ratio of nitrogen-doped graphene, copper nitrate, titanium tetrachloride, and boric acid is 1:(1.5-1.8):(0.1-0.2):(0.3-0.5).
6. The process for preparing a thick film circuit board based on thick film copper metal ceramic according to claim 1, characterized in that: The preparation method of the adhesive is as follows: (1) in a nitrogen atmosphere, methyl methacrylate, acrylamide, 2-butyl methacrylic acid, and azobisisobutyronitrile are added to toluene in sequence, the temperature is set to 60-80° C., and the mixture is stirred for reaction for 2-4 hours; cysteine is added dropwise, and the reaction is continued for 1-2 hours; the product is washed with n-hexane and dried to obtain an acrylic copolymer; (2) the acrylic copolymer is added to dimethylformamide, an epoxy silane coupling agent is added, the mixture is stirred for reaction at 80-85° C. for 1-2 hours, and the mixture is washed and dried to obtain an adhesive.
7. A process for preparing a thick film circuit board based on thick film copper metal ceramic according to claim 6, characterized in that: In the raw materials of the acrylic copolymer, the molar ratio of methyl methacrylate, acrylamide, 2-butyl-methacrylic acid and cysteine is (35-38):(4-7):58:3; in the raw materials of the adhesive, the mass ratio of the acrylic copolymer to the epoxy silane coupling agent is 1:0.1-0.
2.
8. The process for preparing a thick film circuit board based on thick film copper metal ceramic according to claim 1, characterized in that: The solvent comprises dimethylformamide, terpineol, diethylene glycol butyl ether and deionized water in a mass ratio of 50:(40-43):(5-8):
2.
9. The process for preparing a thick film circuit board based on thick film copper metal ceramic according to claim 1, characterized in that: The heating rate of the pre-baking is 5-6°C / min; the heating rate of the intermediate baking is 10-15°C / min; the heating rate of the primary calcination is 65-75°C / min; and the heating rate of the secondary calcination is 50-60°C / min.
10. The process for preparing a thick film circuit board based on thick film copper metal ceramic according to claim 1, characterized in that: The thickness of the thick copper layer is 30-80 μm.
Citation Information
Patent Citations
Graphene composite copper thick film conductive slurry and preparation method thereof
CN104021842A
Copper conductive ink containing graphene oxide, and preparation method and application thereof
CN106167654A
Conductive copper membrane for achieving air glue discharging for low temperature co-fired ceramic and preparation method of conductive copper membrane
CN107799197A
Graphene / base metal alloy conductive material, resistance paste, heating element and preparation method thereof, and application of heating element
CN110519870A
Thick film paste and ceramic circuit board
JP2001202823A
Cited By
Through hole metallization method and metallized glass substrate
CN120432388A
Via metallization method and metallized glass substrate
CN120432388B